CORRUPTION: A LONG-LASTING HISTORICAL DISEASE INFECTING THE INTEGRITY OF THE POLICE - Meini, Bruno (Journal of Anti-Corruption Law, 2023)
Police actions require a high level of integrity, accountability, and transparency. “Police integrity” refers to the demonstration of the qualities of reliability, honesty, and respectability in police work. These are the most important qualities required for all police officers when carrying out their duties and that are necessary to maintain trust in law enforcement agencies. “Police accountability” refers to the high expectation placed on police officers and police departments to act responsibly within the boundaries of the law in ensuring the safety and security of citizens. Transparency in policing aims to make both rules and procedures easily accessible to the public, unless there is a legal reason for keeping them confidential. If police departments do not strictly adhere to the principles of integrity, accountability, and transparency, the risk is that their members will feel less inhibited to abuse their legal powers for personal benefit. Police corruption is, therefore, a specific form of police misconduct aimed at obtaining personal benefits, gained through a criminal modus operandi. The purpose of this article is to discuss and analyse police corruption and to recommend measures which can effectively prevent, combat, and reduce this problem.